Relationship of Logic and Art - Durhan, Gülümser (Fırat University, 2021)
Logic is a formal science that makes it possible to distinguish true statements from false ones through reasoning methods. This reasoning is sometimes an inference from speech, sometimes an inference from visual symbols. With this, the relationship between logic and art is understood. Because art takes place in all the methods used in the expression of creativity and imagination by human hands. The idea that art have aesthetic concern and is not an attempt to prove an idea made us think that art and logic cannot be associated. Although logic is an attempt to reach the truth through reasoning, art provides an inference from its interlocutor by revealing the same reasoning visually or verbally. Art presents the reasoning used by logic in an aesthetic manner. However, while logic is the proof of a single thought because it is the science of proof, art is open-ended and everyone can find something in it, this is the difference from logic as art's adaptation to aesthetic concern. Therefore, the aim of the study is to determine different and common points of logic and art and to examine the connection between them.

Mantık, akıl yürütmeler yolu ile doğruyu yanlıştan ayırt etmedir. Bu akıl yürütme, bazen söylenen sözlerden elde edilen bir çıkarım, bazen de görsel simgelerden ortaya konan bir çıkarsamadır. Bununla mantığın, sanatla olan ilişkisi anlaşılmaktadır. Zira sanat; yaratıcılığın ve hayal gücünün insan eliyle dışavurumunda kullanılan yöntemlerin tümü şeklinde gerçekleşmektedir. Sanatın, estetik kaygı taşıdığı ve bir düşünceyi ispat etme girişimi olmadığı düşüncesi, sanat ile mantığın ilişkilendirilemez olduğu fikrini doğurmuştur. Mantık, akıl yürütmeler sayesinde hakikate ulaşma girişimi ise de sanat, aynı akıl yürütmeleri görsel veya sözsel tarzda ortaya koyup muhatabından bir çıkarsama yapmasını sağlamaktadır. Mantığın kullandığı akıl yürütmeyi sanat, estetiksel tarzda dışarıya sunmaktadır. Ancak mantık, ispat ilmi olması nedeniyle tek bir düşüncenin kanıtı iken, sanat; açık uçludur ve herkes onda kendinden bir şey bulabilir; bu sanatın estetik kaygısına uyum sağlaması olarak mantıktan ayrıldığı noktadır. Dolayısıyla bu çalışmanın amacı, mantık ve sanatın ayrıldığı ve ortak olduğu noktalarının tespit edilmesi yoluyla mantık ve sanat ilişkisinin incelenmesidir.
MANTIK VE SANAT İLİŞKİSİ